Guiding Principles and Practices for Healthcare Outbreak Notification and Disclosures: CORHA Policy Workgroup Framework. (October 2020) - Tierney, Maureen; Kim, Moon; Baliga, Christopher; Ngoh, Martha; Perkins, Kiran; Kainer, Marion; McGiffert, Lisa; Martinello, Richard; Allen, Meredith; Heyer, Kate; Tomlinson, Lisa; Perz, Joseph; et al.
Abstract : Background: Outbreaks of infections in healthcare negatively impact patient outcomes and experience. Transparency is critical to engendering trust and optimizing health. Consistent guidance is not available regarding when to report a possible outbreak of healthcare-associated infections (HAIs) to public health and when to notify a limited population or to publicly disclose the occurrence of HAI. Recent analyses of state public health policies revealed that most states address reporting of outbreaks using terms such as clusters, unusual occurrences, or incidences over baseline. Specific wording about healthcare outbreaks or guidance for notifying patients or public is often absent. Thus, HAI outbreak notification and disclosure guidance and practices vary significantly around the country. A best-practice guidance document will provide clarity for when such reporting should occur. Methods: The Council for Outbreak Response: HAI and Antimicrobial-Resistant Pathogens (CORHA) has undertaken the task of developing this guidance by forming a multidiscipline policy work group with representation from its partner organizations. This work group has been tasked with creating a general framework that will guide notification and disclosure in the context of a possible HAI outbreak. The draft guidance document has been developed over several months of telephone and in-person conferences among work group members. Results: The standardized actions stemming from the guiding principles and recommended practices for conducting step 1 (immediate notification, initial and critical communications that occur when an outbreak is first suspected), were arranged in a table format with rows representing stakeholders and constituents to be notified and columns demonstrating the actions to be taken (Fig. 1). As an investigation progresses, notification should be revisited, especially if an investigation's scope expands. The principles and practices for step 2 (expanded notification) have also been drafted in a table format. Next, the draft guidance addresses step 3 (public disclosure), outlining indications, practical guidance, and considerations in an outline and/or summary format. Real-world examples demonstrating application of the framework are being developed as supplementary resources to the framework. Current work group activities include engaging bioethicists, media reporters and patient advocates to review and comment on the guidance to ensure that it is clear, consistent and practical. Discussion: The draft guidance provides a framework for standardized actions for HAI outbreak notification and disclosure in a stepwise fashion, modeling public health practices and grounded in bioethical principles. The final product will provide valuable, practical advice for effectively sharing information with affected or potentially affected individuals and their caregivers in a timely manner. Funding: None Disclosures: Dawn Terashita reports that her spouse has received honoraria rom the speaker's bureaus of Novo Nordisk and Abbott.